Gestão acadêmica no ensino superior: proposta de informatização do controle de vagas dos cursos de graduação da Universidade Federal do Triângulo Mineiro (UFTM) - REZENDE, Raul Sérgio Reis (2019)
This dissertation presents a proposal for the development of a computerized module for the Academic Control System (SISCAD) to be used at the Universidade Federal do Triângulo Mineiro. This module aims to manage the initial student enrollment openings created at each selective admission process at the university, registering their creation, occupation, re-occupation, whenever possible, their timespan and term of validity. It is understood that the remaining openings, if not filled, are considered a social, academic and economic waste of public order, being a source of idleness of teachers, employees, equipment and physical space. Thus, with accurate and updated data in each academic record event, the module proposed in this thesis may allow for more agility in the sectors responsible for proposing selective processes for student re-admission, enrollment of applicants who seek a second graduation, and transfers. The proposed module, as a technological tool, will contribute to a more efficient management of the openings, contributing to future decision-making, consequently allowing the university to fulfill its social role and maximize the use of its physical structure and existing human resources; in addition to generating a database that, over time, can support more in-depth studies related to student enrolment.